The pottery of Morro of Eten in the Northern Peruvian: a chrono- stylistic approach - Nicolas Lorenzo, Dennis (2023)
This article presents a chrono-stylistic approach to ceramics from Morro de Eten, which was discussed as exclusive to the Late Formative. Based on a stylistic characterization combined with the comparison criterion by similarity, the existence of ceramics linked to the Middle Formative B (1000 - 800 B.C.), Late Formative A (800 - 700 B.C.) and Late Formative B ( 700 – 550 B.C.). In this way, three stylistic phases are established that indicate the prolonged occupation of the site with various types of ceramics, whose shared parallels would be manifesting the complex mechanisms of social interaction in which the inhabitants of Morro de Eten were involved during the Middle and Late Formative.